2018
DOI: 10.1093/molbev/msy088
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Theory and Rapidly Evolving Viral Pathogens

Abstract: The evolution of viral pathogens is shaped by strong selective forces that are exerted during jumps to new hosts, confrontations with host immune responses and antiviral drugs, and numerous other processes. However, while undeniably strong and frequent, adaptive evolution is largely confined to small parts of information-packed viral genomes, and the majority of observed variation is effectively neutral. The predictions and implications of the neutral theory have proven immensely useful in this context, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 105 publications
1
60
0
1
Order By: Relevance
“…Although this moulding process equates ultimate virus evolutionary rates to those of their hosts, the niche perspective is also fully consistent with the hypothesis of neutral evolution of viruses over the much shorter periods of virus evolution observed in contemporary virus samples (as discussed in ref. 87 ). Indeed, more than any other factor, the idea that host-adapted viruses are exploring space around a small cage of tolerated substitutions accounts best for the absurdly different short-term and long-term substitution rates they display over differing evolutionary timescales.…”
Section: Discussionmentioning
confidence: 99%
“…Although this moulding process equates ultimate virus evolutionary rates to those of their hosts, the niche perspective is also fully consistent with the hypothesis of neutral evolution of viruses over the much shorter periods of virus evolution observed in contemporary virus samples (as discussed in ref. 87 ). Indeed, more than any other factor, the idea that host-adapted viruses are exploring space around a small cage of tolerated substitutions accounts best for the absurdly different short-term and long-term substitution rates they display over differing evolutionary timescales.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that mutations with a functional impact almost invariably carry a fitness cost, but are frequently compensated by subsequent fitness restoring or permissive mutations (Frost, et al 2018 Structural models showing the parallel mutation identified (highlighted in red). Only negative ddG values are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence for gene-wide pervasive positive selection was detected, suggesting that the proportion of positively selected sites is very small compared to that of sites evolving under nearly neutral or purifying selection (Suzuki 2006), consequently returning global ω (dN/dS ratio) values of < 1. Whilst positive selection plays a crucial role in fixing beneficial and compensatory mutations, permissive mutations are likely fixed through linkage and soft sweeps from the standing genetic variation (Frost, et al 2018). Thus, we show evidence that most parallel mutations, if they adaptive, represent permissive changes that can occur anywhere throughout the viral genome and are fixed through linkage and genetic sweeps before an outbreak.…”
Section: Molecular Selection Analysis Of Parallel Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-1, Influenza viruses, SARS-CoV and hepatitis C virus) pointed towards the rapidly evolving nature of the viral genomes and are subjected to the strongest evolutionary forces. The ability to undergo host-specific adaptive changes in the viral genomes has enabled them to escape the innate as well as adaptive immune responses, acquire resistance towards drugs or infect new hosts (Frost et al, 2018). The rapid spread of SARS-CoV-2 around the world has enabled exposure of the virus to individuals with diverse genetic and immunological backgrounds having varied demographics (age, sex, environmental conditions, etc.)…”
Section: Sars-cov-2 Like Sars-cov and Mers-cov Belongs To The Genus Bmentioning
confidence: 99%